2016
DOI: 10.1158/0008-5472.can-15-3342
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent PPP2R1A Mutations in Uterine Cancer Act through a Dominant-Negative Mechanism to Promote Malignant Cell Growth

Abstract: Somatic missense mutations in the Ser/Thr protein phosphatase 2A (PP2A) Aα scaffold subunit gene PPP2R1A are among the few genomic alterations that occur frequently in serous endometrial carcinoma (EC) and carcinosarcoma, two clinically aggressive subtypes of uterine cancer with few therapeutic options. Previous studies reported that cancer-associated Aα mutants exhibit defects in binding to other PP2A subunits and contribute to cancer development by a mechanism of haploinsufficiency. Here we report on the fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(137 citation statements)
references
References 55 publications
11
124
2
Order By: Relevance
“…S3A). In addition, it was recently shown that disruption of interactions between PP2A core enzyme and canonical B subunits by mutations in PP2A Aα (P179R, R18G) promotes PP2A interactions with members of the STRIPAK complex (Haesen et al 2016), reinforcing the notion that ST phenocopies the effect of cancer-associated PP2A mutations. More generally, these observations suggest that striatins act as key regulators of PP2A that impart substrate specificity.…”
Section: Discussionmentioning
confidence: 80%
“…S3A). In addition, it was recently shown that disruption of interactions between PP2A core enzyme and canonical B subunits by mutations in PP2A Aα (P179R, R18G) promotes PP2A interactions with members of the STRIPAK complex (Haesen et al 2016), reinforcing the notion that ST phenocopies the effect of cancer-associated PP2A mutations. More generally, these observations suggest that striatins act as key regulators of PP2A that impart substrate specificity.…”
Section: Discussionmentioning
confidence: 80%
“…PPP2R1B is reported to be downregulated in cultured dermal fibroblasts from patients with systemic sclerosis, a fibrotic disorder . The reported PPP2R1A activating mutation (p.S256F) is shown recently in endometrial cancer cells to behave in a dominant‐negative manner due to gain‐of‐function interactions with the PP2A inhibitor TIPRL1, resulting in hyperphosphorylation of AKT, GSK3β, and mTOR signaling pathways . That is, the activating mutation leads to reduced PP2A activity and consequent increased AKT activity.…”
Section: Mutations Of Cancer Driver Genes In Endometriosis and Their mentioning
confidence: 99%
“…Remarkably, based on structural studies, the same residues or neighbouring residues were predicted to be important for interaction with the B subunits [133,148]. However, experimental evidence for this hypothesis revealed a much more sophisticated image, in that mutations at these positions indeed resulted in binding deficiencies of Aα mutants with several regulatory B subunit types, but specifically preserved binding to others, most notably to B56δ and B56γ [149,150]. Some mutations, e.g., p.(P179R), also diminished binding to the catalytic C subunit [149].…”
Section: Therapeutic Potential Of Targeting Kinases and Phosphatasmentioning
confidence: 99%
“…However, experimental evidence for this hypothesis revealed a much more sophisticated image, in that mutations at these positions indeed resulted in binding deficiencies of Aα mutants with several regulatory B subunit types, but specifically preserved binding to others, most notably to B56δ and B56γ [149,150]. Some mutations, e.g., p.(P179R), also diminished binding to the catalytic C subunit [149]. Moreover, Haesen et al suggested a dominant negative mechanism for these mutants, as the PP2A trimers that could still be formed proved catalytically impaired through the increased recruitment of a cellular PP2A inhibitor, TIPRL1 [149].…”
Section: Therapeutic Potential Of Targeting Kinases and Phosphatasmentioning
confidence: 99%
See 1 more Smart Citation